Strenthening of UMP core values in engineer huffaz programs and the challenges of the 4th industrial revolution: an analysis in the University Malaysia Pahang - Rashidi, Abbas; Syafrimen,; Nova, Erlina (HLCB, 2018)
This study examines the engineer huffaz programs and the challenges in facing the current 4th industrial revolution (IR 4.0). Respondents of the research are consisting of 15 students from the faculty of mechanical, electrical and manufacturing engineering at Pekan campus which are selected in the tahfiz program conducted by the Center for Modern Languages and Human Sciences with the Islamic Centre and Human Development (PIMPIN). The methodology used is this research was document analysis and program observation in line with UMP core values. This study demonstrated that the first core value agreed by the UMP's top management is the strong relationship with the Creator, in the context of this engineer huffaz activities program, revelation knowledge has been integrated with engineering knowledge to uplift the spiritual aspects. The values of the Quran are incorporated together with the value of science and technology for the teachings in the tahfiz programs. The core values which are nurtured in the huffaz program are in tandem with the industrial revolution 4.0 needs. This core value creates a steadfast student in upholding shared principles and resolute in facing challenges.